Fungal communities associated with species of Fraxinus tolerant to ash dieback, and their potential for biological control - Chatchai Kosawang (2018)
© 2017 British Mycological Society. Ash dieback, caused by the fungus Hymenoscyphus fraxineus, has threatened ash trees in Europe for more than two decades. However, little is known of how endophytic communities affect the pathogen, and no effective disease management tools are available. While European ash (Fraxinus excelsior) is severely affected by the disease, other more distantly related ash species do not seem to be affected. We hypothesise that fungal endophytic communities of tolerant ash species can protect the species against ash dieback, and that selected endophytes have potential as biocontrol agents. These hypotheses were tested by isolating members of the fungal communities of five tolerant ash species, and identifying them using Intergenic Transcribed Spacer (ITS) regions. Candidate endophytes were tested by an in vitro antagonistic assay with H. fraxineus. From a total of 196 isolates we identified 9 fungal orders, 15 families, and 40 species. Fungi in orders Pleosporales, such as Boeremia exigua and Diaporthe spp., and Hypocreales (e.g., Fusarium sp.), were recovered in most communities, suggesting they are common taxa. The in vitro antagonistic assay revealed five species with high antagonistic activity against H. fraxineus. These endophytes were identified based on ITS region as Sclerostagonospora sp., Setomelanomma holmii, Epicoccum nigrum, B. exigua, and Fusarium sp. Three of these taxa have been described previously as antagonists of plant pathogenic microbes, and are of interest for future studies of their potential as biological control agents against ash dieback, especially for valuable ash trees in parks and urban areas.